Chronic mild stress impact: are females more vulnerable? - Dalla, C; Antoniou, K; Drossopoulou, G; Xagoraris, M; Kokras, N; Sfikakis, A; Papadopoulou-Daifoti, Z. (Neuroscience, 2005)
Despite the knowledge that women are more susceptible than men to stress-related mental illness, such as major depression, there is no comprehensive estimation of the role of gender in the detrimental effects of chronic stress that might cause depression. Sex differences regarding the association of behavioral parameters with serotonergic and hypothalamic-pituitary-adrenal axis activities were investigated in the chronic mild stress model of depression. Additionally, the impact of chronic mild stress exposure on an additional/novel short-term stressful procedure, such as the forced swim test was examined in male and female rats. Female rats were found to be more vulnerable to chronic mild stress and that was depicted with disruption of sucrose intake, decreases in open field activity, increased corticosterone levels, alteration in estrous cycle and decreased serotonergic activity in hippocampus and hypothalamus. On the contrary, in males the current chronic mild stress protocol elicited only behavioral changes, such as disruption in sucrose intake and decreased open field activity. Interestingly, in response to forced swim test, females previously subjected to chronic mild stress, were found to cope better by exhibiting increased active behavior in the second forced swim test session and higher hypothalamic serotonergic activity in comparison with corresponding males. On the other hand, males were more affected by previous chronic mild stress exposure and that was manifested by decreased active behavior in the first forced swim test session and increased corticosterone levels following second forced swim test session. These data indicate that although females are more vulnerable in the application of chronic mild stress than males, in response to an additional-novel stressor (forced swim test) they show better response. Therefore, both sex/gender and combination of stressful procedures should be carefully considered in the study of the pathophysiology of stress-related mental illnesses.
Keywords: Animals; Behavior, Animal/physiology; Brain Chemistry/physiology; Brain/physiopathology; Chronic Disease; Corticosterone/metabolism; Feeding Behavior/physiology; Female; Food Deprivation/physiology; Male; Neurotransmitter Agents/metabolism; Photic Stimulation; Rats; Rats, Wistar; Serotonin/metabolism; Sex Characteristics; Stress, Psychological/metabolism/*physiopathology; Swimming/psychology; Synaptic Transmission/physiology; Water Deprivation/physiology